Britain in close-up [an in-depth study of the changing face of contemporary Britain] - McDowall, David 1945- (Longman, 1993)
A study of a range of aspects of contemporary Britain, including government and politics, society and culture, education and religion. In examining the changes which the nation is undergoing, it offers a vision of Britain's future in the 21st century. Exer.